2013
DOI: 10.1111/jhn.12056
|View full text |Cite
|
Sign up to set email alerts
|

Promoting dietary diversity to improve child growth in less‐resourced rural settings in Uganda

Abstract: Educating caregivers has the potential to improve young children's nutritional status and growth, especially among less literate populations where households subsist on what they produce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The dietary diversity score (DDS) is one of the a priori defined dietary indices used to assess overall diet quality [ 9 ]. Dietary diversity has been known as a key index of high diet quality in various populations [ 10 12 ]. Nevertheless, the association between dietary diversity and obesity remains controversial across different cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary diversity score (DDS) is one of the a priori defined dietary indices used to assess overall diet quality [ 9 ]. Dietary diversity has been known as a key index of high diet quality in various populations [ 10 12 ]. Nevertheless, the association between dietary diversity and obesity remains controversial across different cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Food consumption is one of the most important factors in the aetiology of nutritional anaemia and iron deficiency (ID) in school-aged children (4,5) . The intake of a great variety of foods across and within the various food groups is needed to meet nutrient requirements and may help to alleviate multiple micronutrient deficiencies and reduce the risk of nutritional anaemia (6)(7)(8) . In low-and middleincome countries, including South Africa, the diets of the majority of children lack variety and consist mainly of plant-based foods (predominantly cereals, roots and tubers), with limited consumption of animal-source foods (ASF), fruits and vegetables (6,(9)(10)(11) .…”
mentioning
confidence: 99%
“…The key messages adapted to support the food guide were designed to address information gaps identified in a needs assessment study reported by Nankumbi et al [7]. Age appropriate IYCF cards [19], which are the standard tool for educating caregivers of young children in Uganda, were used as the reference in developing the nutrition education messages. 2 provides an outline of key messages communicated using the cards.…”
Section: Description Of the Nutrition Education Interventionsmentioning
confidence: 99%
“…This indicates that the Food Guide group adapted better child-feeding practices than caregivers in the IYCF group and the control. The similarity between the IYCF group and the control may be attributed to the likely use of IYCF counselling cards during the well-child visits (mainly immunization days) in public health facilities to educate caregivers on appropriate child-feeding practices in both the IYCF cards and control group since use of IYCF cards is the standard practice [19]. This indicates that community level nutrition education that utilizes the current IYCF counselling cards is likely not to have added much advantage in improving overall child-feeding practices compared to ongoing IYCF education efforts in public health facilities.…”
Section: Socio-demographic Characteristics Of the Participantsmentioning
confidence: 99%
See 1 more Smart Citation